Hydrocortisone supresses inflammatory activity of metalloproteinase - 8 in carotid plaque - Gabriel,Sthefano Atique (2015)
AbstractObjective:Matrix metalloproteinases are inflammatory biomarkers involved in carotid plaque instability. Our objective was to analyze the inflammatory activity of plasma and carotid plaque MMP-8 and MMP-9 after intravenous administration of hydrocortisone.Methods:The study included 22 patients with stenosis ≥ 70% in the carotid artery (11 symptomatic and 11 asymptomatic) who underwent carotid endarterectomy. The patients were divided into two groups: Control Group - hydrocortisone was not administered, and Group 1 - 500 mg intravenous hydrocortisone was administered during anesthetic induction. Plasma levels of MMP-8 and MMP-9 were measured preoperatively (24 hours before carotid endarterectomy) and at 1 hour, 6 hours and 24 hours after carotid endarterectomy. In carotid plaque, tissue levels of MMP-8 and MMP-9 were measured.Results:Group 1 showed increased serum levels of MMP- 8 (994.28 pg/ml and 408.54 pg/ml, respectively; P=0.045) and MMP-9 (106,656.34 and 42,807.69 respectively; P=0.014) at 1 hour after carotid endarterectomy compared to the control group. Symptomatic patients in Group 1 exhibited lower tissue concentration of MMP-8 in comparison to the control group (143.89 pg/ml and 1317.36 respectively; P=0.003). There was a correlation between preoperative MMP-9 levels and tissue concentrations of MMP-8 (P=0.042) and MMP-9 (P=0.019) between symptomatic patients in the control group.Conclusion:Hydrocortisone reduces the concentration of MMP- 8 in carotid plaque, especially in symptomatic patients. There was an association between systemic and tissue inflammation.